2018
DOI: 10.1080/87565641.2018.1540007
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Executive Dysfunction, Fatigue, and Psychological and Emotional Symptoms in Physically Well-Functioning Long-Term Survivors of Pediatric Brain Tumor

Abstract: Completing this thesis has been one of most arduous ordeals I have taken on, but also one of the most educational, satisfying, and now at the end of it all, liberating, empowering and relieving experiences I might ever have had. The relief of completing is most likely not only felt by me; I imagine several people around me may feel somewhat relieved themselves to see that I finally reached the finish line. Parallel to working on this thesis, these years since I first started have been the most eventful of my l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 157 publications
(320 reference statements)
2
34
1
Order By: Relevance
“…Regarding psychosocial outcomes, a total of 44 specific outcomes under 18 different names appeared in eight of the 10 quantitative studies. The 44 specific outcomes were further coded into five relatively broad categories: (1) academic self-efficacy, referring to students' self-perceived confidence to tackle new learning tasks, improve skills, or grasp course materials (Bandura, 1997); (2) goal valuation, regarding whether students value a learning task and find it meaningful enough to do the work (Siegle, 2013); (3) environmental perceptions, concerning how students feel about the atmosphere of their environments, such as finding teachers to be supportive or feeling insecure around other classmates (Siegle et al, 2017); (4) self-regulation/ motivation as a psychosocial outcome category encompassing activities, beliefs, or behaviors relevant to self-regulated learning or achievement motivation (McCoach & Siegle, 2003a); and (5) psychosocial functioning, referring to a variety of mental, social, or emotional states or experiences, such as anxiety, depression, self-consciousness, distress, loneliness, feeling of belonging, or learned helplessness (Puhr et al, 2019;Ziolkowski et al, 2019).…”
Section: Study Codingmentioning
confidence: 99%
“…Regarding psychosocial outcomes, a total of 44 specific outcomes under 18 different names appeared in eight of the 10 quantitative studies. The 44 specific outcomes were further coded into five relatively broad categories: (1) academic self-efficacy, referring to students' self-perceived confidence to tackle new learning tasks, improve skills, or grasp course materials (Bandura, 1997); (2) goal valuation, regarding whether students value a learning task and find it meaningful enough to do the work (Siegle, 2013); (3) environmental perceptions, concerning how students feel about the atmosphere of their environments, such as finding teachers to be supportive or feeling insecure around other classmates (Siegle et al, 2017); (4) self-regulation/ motivation as a psychosocial outcome category encompassing activities, beliefs, or behaviors relevant to self-regulated learning or achievement motivation (McCoach & Siegle, 2003a); and (5) psychosocial functioning, referring to a variety of mental, social, or emotional states or experiences, such as anxiety, depression, self-consciousness, distress, loneliness, feeling of belonging, or learned helplessness (Puhr et al, 2019;Ziolkowski et al, 2019).…”
Section: Study Codingmentioning
confidence: 99%
“…Self-reported executive dysfunction, fatigue, and psychological and emotional symptoms in physically well-functioning long-term survivors of pediatric brain tumor (Puhr et al, 2019a).…”
Section: Paper Imentioning
confidence: 99%
“…20,28,29 One large case-control study out of Norway identified that brain tumor survivors show clear deficits across emotional control, task initiation, working memory, organization, self-monitoring, and task monitoring. 30 Furthermore, memory issues have been identified in cohorts of brain tumor survivors, ranging from poor performance in recall to recognition to immediate memory. 29,31 Deficits in attention and processing speed are also common.…”
mentioning
confidence: 99%